The Tripartite Principle of The Psyche of Main Character The Power of the Dog Film (2021) - Sari, Dewi; Valiantien, Nita Maya; Nasir, Muhammad Alim Akbar (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2025)
This research aimed to analyze the personality dynamics of Phil Burbank, the main character in the film The Power of the Dog, through the lens of Sigmund Freud’s psychoanalysis theory on the concept of the tripartite principle of the psyche: id, ego, and superego. The 2021 film The Power of the Dog, written and directed by Jane Campion, and its script were used as the primary data source. This research employed a qualitative method and a psychoanalysis approach to examine how these three components of personality interacted within Phil Burbank. Phil Burbank was portrayed as a dominant masculine figure who harbored deep and complex inner conflicts, based on the categorization of the situation, identified in Phil’s aggressive behaviour and his need to dominate those around him, reflecting unsublimated unconscious drives. The ego was observed in his attempts to conform to social norms and preserve his masculine image despite internal conflict with his desires. The superego was manifested through moral judgments and efforts to uphold internalized morality, shaping his attitudes and worldview. The results indicated that the id was the most dominant structure with eight data, followed by ego with four data, and superego with two data. Concluded from this research was the idea that Phil’s inability to reconcile his desires (id), his social façade (ego), and his moral conscience (superego) led to his self-destruction. This psychological imbalance was reflected in emotional instability, toxic relationships, and ultimately, his death.